Open source software for library systems – 2. Issue 9 (7th November 2016) - Oyelude, Adetoun A.
Abstract : Purpose: This paper aims to concentrate on reviewing articles on open source software (OSS), found on the internet, that were published in the year 2016. Design/methodology/approach: A critical look is taken at OSS generally as found in the literature and also on the commonly used OSS in libraries and information science work or research work. Findings: It is hoped that this review will assist in pointing out the trends and aid in informed decision-making, as it concerns OSS. Social implications: Akintomide (2016) described OSS as a part of human existence which is exhibited in mobile devices that run on the android operating system, to computers, laptops and servers that run on the Linux operating system, to other software (Library management software inclusive) that are open access. Originality/value: The openness of it makes the users (libraries and scholars) leave documentation that steers how the open software technologies are implemented and by whom. They are free, have used communities, are vetted by users and are constantly in development.